Pharmacokinetic Modeling to Guide Preclinical Development of an Islatravir-Eluting Reservoir-Style Biodegradable Implant for Long-Acting HIV PrEP - Talisa S. Kinsale; Mackenzie L. Cottrell; Linying Li; Rhonda Brand; Greg Gatto; Ellen Luecke; Chasity Norton; Archana Krovi; Julie B. Dumond; Gauri Rao; Shekhar Yeshwante; Brian Van Horne; et al. (MDPI AG, 2024)
Long-acting injectable cabotegravir is more effective than daily oral PrEP at preventing HIV transmission due to improved adherence, but requires bi-monthly large-volume intramuscular injections. Subcutaneous (SC) contraceptive implants can be formulated with antiretrovirals for extended-duration HIV PrEP. Islatravir (ISL) is a first-in-class, investigational antiretroviral with pharmacologic properties well-suited for implant delivery. We performed preclinical studies for the development of a reservoir-style, poly(ε-caprolactone) ISL-eluting implant by conducting a single-dose SC ISL dose-ranging pharmacokinetic (PK) study of 0.1, 0.3, and 1 mg/kg in adult Wistar rats. Non-compartmental analysis was conducted, and dose proportionality assessed for ISL plasma and intracellular islatravir-triphosphate (ISL-tp). Population PK models estimated ISL's unit impulse response to deconvolve ISL-implant in vivo absorption rate (mg/day) and cumulative mass (mg) from published rat plasma PK (n = 10). Drug release was interpreted using four kinetic models. Dose proportionality was affirmed for ISL and ISL-tp. A first-order, two-compartment model fitted the SC ISL bolus data. Mean (SD) absorption rate from 0 to 154 days was 0.072 ± 0.024 mg/day, and cumulative mass at 154 days was 8.67 ± 3.22 mg. ISL absorption was well-described by zero-order (r2 = 0.95) and Ritger-Peppas (r2 = 0.98). Our zero-order ISL-release poly(ε-caprolactone) implant is projected to achieve clinical PK above ISL-tp's PrEP efficacy threshold. Continued development for HIV PrEP applications is warranted.